Cu role in the optical constants of Cu2xGe40−xS60−x films for optoelectronics and photovoltaic applications - Kamal Abdel-Nabi Aly; Sabry A. Mohamed; Yasser B. Saddeek (Journal of Taibah University for Science)
Physical characteristics of ternary glasses based on sulphur, are the main topic of the investigation. Cu2xGe40−xS60−x (0 ≤ x ≤ 8 at. %) chalcogenides was fabricated using the conventional melt-quench method. With an increase in Cu-concentration, the glass's density (ρ) increased but the molar volume (Vm) decreased. Transmittance and reflection measurements of the films were made over 0.35–2.5 µm spectral-range. The estimated envelopes (RM, Rm) of the reflection spectrum might be used to determine the complex refractive index and the film thickness. With increasing Cu-concentrations, the refractive index (n) increased while the optical gap (Eg) decreased. Cu-concentrations affects the film's nonlinear refractive index (n2), 3ed-susceptibility (χ(3)) and nonlinear absorption coefficient (χa) were investigated. In Cu2xGe40−xS60−x system, the n2, χ(3), and χa values increase with the Cu-additions. Finally, the films analyzed here exhibit interesting properties for application in various optical devices.